2017
DOI: 10.1177/0038026117691718
|View full text |Cite
|
Sign up to set email alerts
|

Parenting teenagers as they grow up: Values, practices and young people’s pathways beyond school in England

Abstract: Parents' values and practices are central to theorising the reproduction of inequality across generations. Where researchers have explored how parental values and practices relate to class circumstances and their combined influence on children's outcomes, the focus has been largely on younger families, with limited evidence on parents' perspectives at the point children approach and pass compulsory school leaving age. The trebling of university tuition fees in England, the insecurity which characterises many n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Anthony Giddens' theory of reflexive self-narratives (1991) has been beneficial for understanding identities over time and how people author themselves through narratives, but it is criticised for not taking into account that social context is still part and parcel of people's possibilities and self-narratives (Thomson, 2011;Walkerdine, Lucey, & Melody, 2001). Irwin (2018) argues that there is a tradition in British and US qualitative sociology of suggesting a causal relationship between class positioning and parenting styles, particularly since Lareau (2003) in the United States suggested that the middle-class parented their children in a mode of concerted cultivation and the working class as natural growth. Parents' involvement with their children in this body of research has mostly been investigated from the parents' point of view (Maxwell & Aggleton, 2013).…”
Section: Parenting Class Diversity and School Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthony Giddens' theory of reflexive self-narratives (1991) has been beneficial for understanding identities over time and how people author themselves through narratives, but it is criticised for not taking into account that social context is still part and parcel of people's possibilities and self-narratives (Thomson, 2011;Walkerdine, Lucey, & Melody, 2001). Irwin (2018) argues that there is a tradition in British and US qualitative sociology of suggesting a causal relationship between class positioning and parenting styles, particularly since Lareau (2003) in the United States suggested that the middle-class parented their children in a mode of concerted cultivation and the working class as natural growth. Parents' involvement with their children in this body of research has mostly been investigated from the parents' point of view (Maxwell & Aggleton, 2013).…”
Section: Parenting Class Diversity and School Stressmentioning
confidence: 99%
“…Parents' involvement with their children in this body of research has mostly been investigated from the parents' point of view (Maxwell & Aggleton, 2013). With Lareau's and related theories as a starting point, much class and ethnicity research has investigated how parents influence their children in terms of 'resourcing' them (Stefansen & Aarseth, 2011), in terms of deciding on future educational trajectory (Hegna & Smette, 2017;Irwin, 2018;Irwin & Elley, 2013;Kindt, 2017) and in terms of installing an entitlement to success (Gillies, 2005) or different forms of motivation (Aarseth, 2017). The parental strategies of the middle classes are often analysed in terms of their emotional work to struggle upwards-as a 'fear of falling' or a way of anxiously installing autonomy and self-drive to maintain their class positions ( (Irwin & Elley, 2011;Vincent & Ball, 2007).…”
Section: Parenting Class Diversity and School Stressmentioning
confidence: 99%
“…A notable shift in scholarly research worldwide is towards the emphasis on ‘intensive parenting’, a term coined by Hays (1996) to describe the child-rearing activity in which parents sacrifice their own needs and spend a tremendous amount of time, energy and money on their children. Parenting, as Budds et al (2017) and Irwin (2018) note, is conditioned by socio-economic resources, with differences manifesting themselves mainly between working- and middle-class families in Western societies. In Lareau’s classic study of the impact of family class on child-rearing, she finds that middle-class American parents are actively engaged in a purposeful, goal-oriented concerted cultivation style of parenting whereas working-class American parents adopt a more laissez-faire, negligent accomplishment of natural growth style of parenting (Lareau, 2003).…”
Section: Introductionmentioning
confidence: 99%